Marxist and non-Marxist aspects of the cultural-historical psychology of L.S. Vygotsky - Veresov, Nikolai (Outlines. Critical Practice Studies, 2005)
It was not only Marxism which influenced Vygotsky. He was a child of the Silver Age of Russian culture and philosophy and the influence of this should not be underestimated. Some traits in Vygotsky’s theory, traditionally considered as Marxist – such as the concept of the social origins of mind or sign as psychological tool have deeper and wider roots in works of Shpet, Blonsky, Sorokin and Meierhold. As for Marxism as such, it must be mentioned that during all three periods of his creative evolution Vygotsky had different approaches to what was true Marxist psychology and how it should be built. These are items this paper is focused on.